WHY DO YOU WANT ME TO LEARN CONNECTIVELY BUT TEST ME INDIVIDUALLY? SOCIALLY EMBEDDED LEARNING AT THE UNIVERSITY - Bielinis, Lidia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Connectivism concept introduced by George Siemens seems to be accurate when considering current-learning processes in higher education. The author emphasises the role of socially embedded learning that can take place out of human bodies, in devices. The main aim of this work was to analyse students’ and academic teacher’s experiences related to cooperating through a network and creating mind maps as a result of learning in the frame of the conducted course at the University. The data was collected during the course through Mentimeter tool, which enabled the author to learn students’ opinions, reflections and associations related to the process of working on electronic mind maps. Students were also asked to write reflective essays where they described their experiences associated to the mind map that were significant from the perspective of learning at the University. The results of the analysis were presented below.